Prognostic value of the CIPA nutritional screening tool in over 30,000 hospitalized patients: a retrospective study (2014–2022) - García Fernández, Javier; Suárez-Llanos, José Pablo; Lorenzo González, Cristina; Márquez Mesa, Elena; García Núñez, María Araceli; Farrais Luis, Maria Demelza; Fuentes Ferrer, Manuel Enrique (Frontiers in Nutrition, 2025)
IntroductionMalnutrition is a well-established negative prognostic factor in hospitalized patients, contributing to increased morbidity and mortality. The CIPA (Control of Food Intake, Protein, and Anthropometry) screening tool was developed to identify patients at nutritional risk and to predict adverse clinical outcomes across both surgical and non-surgical populations. This study aimed to evaluate the prognostic value of the CIPA tool in routine clinical practice by analyzing its association with key clinical outcomes since its implementation at our center in 2014.Materials and methodsWe conducted a retrospective analysis of inpatients screened with the CIPA tool between 2014 and 2022 in a tertiary care hospital. The association between CIPA screening results and clinical outcomes—including 3- and 6-month mortality, early hospital readmission, and length of stay—was assessed, with a particular focus on patients with active oncological disease. Regression analyses were adjusted for age, sex, admitting department, and type of admission.ResultsA total of 30,581 patients were included, of whom 31.4% screened positive for malnutrition using the CIPA tool. CIPA-positive patients had significantly higher mortality at 3 months (adjusted OR 3.02; 95% CI: 2.78–3.30; p < 0.001) and at 6 months (adjusted OR 2.69; 95% CI: 2.49–2.91; p < 0.001). They also exhibited increased rates of early readmission (adjusted OR 1.43; 95% CI: 1.34–1.53; p < 0.001) and a longer median hospital stay (β = 0.25; 95% CI: 0.23–0.27; p < 0.001).DiscussionIn this large, real-world cohort, the CIPA nutritional screening tool was a robust predictor of poorer clinical outcomes among hospitalized patients with positive screening results. These findings support the utility of CIPA screening for early identification of high-risk patients, enabling targeted nutritional interventions to potentially mitigate adverse outcomes.